EFEKTIVITAS BEDSIDE TEACHING TERHADAP PENINGKATAN KOMPETENSI PRAKTIK ASUHAN KEPERAWATAN - Ari Sunari; Maulana Yusuf; Bambang Riyawan; Ayu Listyo D; Imelda (CV. ADIBA AISHA AMIRA, 2025)
Bedside teaching (BST) is a clinical learning method conducted directly at the patient's bedside, involving interactions among nurses, students, and patients. This literature review aims to evaluate the effectiveness of bedside teaching in improving nurses’ competencies in providing nursing care. A systematic review was conducted using ten peer-reviewed articles from national nursing journals, selected based on inclusion criteria such as the implementation of BST and the measurement of competency outcomes. The synthesis results indicate that BST significantly enhances cognitive, psychomotor, and affective competencies in nursing practice. Most studies reported p-values < 0.05, confirming the statistical significance of the intervention. These findings support the broader implementation of BST as an effective educational method in clinical nursing practice to strengthen nurses’ clinical skills and professional behaviors.